Emerging Waveguide Technology 2018
DOI: 10.5772/intechopen.76799
|View full text |Cite
|
Sign up to set email alerts
|

Multimode Waveguides on an SOI Platform for Arbitrary Power Splitting Ratio Couplers

Abstract: Optical power couplers with arbitrary power splitting ratios are important components for many applications such as Mach-Zehnder interferometer-based structures, filters, switches, dispersion compensations, optical interconnects, and microring resonators. In this chapter, we present a new approach to achieve a very high compact coupler with arbitrary power splitting ratios on silicon on insulator (SOI) waveguides. The proposed device requires only one 4Â4 multimode interference (MMI) coupler. We use a passive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…The results suggested that the total device length should be chosen to be 304 μm to achieve the best operation. These results are comparable and consistent with the results estimated using self-imaging theory [6,24].…”
Section: Results and Discussionsupporting
confidence: 92%
“…The results suggested that the total device length should be chosen to be 304 μm to achieve the best operation. These results are comparable and consistent with the results estimated using self-imaging theory [6,24].…”
Section: Results and Discussionsupporting
confidence: 92%